2001
DOI: 10.1002/ijc.1517
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent phosphorylation of CYP2B1 as a functional switch for cyclophosphamide activation and its hormonal controlin vitro andin vivo

Abstract: An important feature of cytochrome P450 (CYP) 2B1 is its high ability to convert the prodrug cyclophosphamide (CPA) to therapeutically cytotoxic metabolites, resulting in interstrand DNA-cross-linking and cell death. We have examined whether and how the phosphorylation of CYP2B1 influences CPA metabolic activation in vitro and in vivo. We found first that only part of the total CYP2B1 pool undergoes phosphorylation. This part is fully inactivated. Second, phosphorylation of CYP2B1 in intact hepatocytes reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Even though such lipid modifications have not been examined with P450, increasing evidence has shown post-translational modifications of P450, including phosphorylation, nitration, and glycosylation, suggesting that the modifications are involved in facilitating the proper catalytic function of P450 (41). For example, phosphorylation was found in many P450s, including CYP2B1, CYP2E1, and CYP3A4, and the modification resulted in modulation of enzyme activity, dual targeting of P450s to the ER and mitochondria, or degradation (42)(43)(44). Further studies are required to determine whether amino acid sequences within the identified regions are targeted for post-translational modifications that may enhance interaction of P450 with specific membrane regions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though such lipid modifications have not been examined with P450, increasing evidence has shown post-translational modifications of P450, including phosphorylation, nitration, and glycosylation, suggesting that the modifications are involved in facilitating the proper catalytic function of P450 (41). For example, phosphorylation was found in many P450s, including CYP2B1, CYP2E1, and CYP3A4, and the modification resulted in modulation of enzyme activity, dual targeting of P450s to the ER and mitochondria, or degradation (42)(43)(44). Further studies are required to determine whether amino acid sequences within the identified regions are targeted for post-translational modifications that may enhance interaction of P450 with specific membrane regions.…”
Section: Discussionmentioning
confidence: 99%
“…Although this sequence of events is certainly plausible, it is highly likely that additional mechanisms, such as phosphorylation, play a role in regulating P450 activity. Indeed, some P450 enzymes (CYP2B1, CYP2B2, and CYP2E1) are reported to be phosphorylated by protein kinase A (PKA), and the consequences of P450 phosphorylation range from the regulation of activity (Oesch-Bartlomowicz et al, 2001) and subcellular localization (Anandatheerthavarada et al, 1999;Korsmeyer et al, 1999) to proteasome degradation (Eliasson et al, 1992;Korsmeyer et al, 1999). Although there has been little advancement in this area over the last few years, other P450 enzymes such as the hepatic-enriched CYP3A4 and CYP2E1 are phosphorylated by PKA and protein kinase C, which accelerates their ubiquitination and endoplasmic reticulumassociated degradation (Correia et al, 2014).…”
Section: A Regulation Of Cytochrome P450 Enzyme Expression and Activitymentioning
confidence: 99%
“…The cAMP signaling pathway also participates in CY metabolism in the liver. 49,50 The appropriate sequential administration of CY and cAMP analogs/PDE4B inhibitors to lymphoma patients may be an effective approach for cancer therapy.…”
Section: Western Blot Analysismentioning
confidence: 99%